PERSEPSI TENTANG PENGALAMAN NEGATIF PENGGUNA ANGKUTAN PUBLIK PERKOTAAN - Rachmatia, Dita; Basuki Joewono, Tri (Jurnal Transportasi, 2009)
The service quality of public transportation in several cities in Indonesia has not fulfilled the expectation yet.There are many negative experiences that have been experienced by the user of public transportation. Thepurposes of this study are to analyze the perception regarding negative experience experienced by the usersof the public transportation in Jakarta, Bandung, Yogyakarta and to compare the perception of negativeexperience in those three cities. The data employed in this study are secondary data. Analysis in this studyapplies the non-parametric statistic method, i.e. k-independent sample and chi-square. The results show thatthere is significant different between perception of the users of public transportation and the negativeexperience in making use of public transportation. Frequencies for each negative experience in those threecities are also significantly different.Keywords: public transportation, quality of service, and perception of negative experience.